What Makes a Difference? Turning Points for Young People in the Process of Leaving Placements in Public Care. - Ingrid Höjer; Yvonne Sjöblom (Social Work & Society, 2014)
The purpose of this study is to examine young care leavers' narrative accounts expressed as turning points connected to their experiences of being in care and leaving care. Telephone interviews were conducted with 65 young people, between 18 and 26 years old, who had left care in Sweden within the time span of previous three months to three years. Altogether, the results suggest that there are both positive and negative turning points connected to the care experience for young care leavers. To develop a trusting relationship to a family member or a significant other, a feeling of being in control of your life and experience an opportunity to change a negative life course are important factors in the young care leaver's accounts about turning points. These factors were also linked to how they interpreted their care experiences and the impact it had on their self-identity and well-being.